Pengaruh Penambahan Cairan Rumen Sapi dan Kambing pada Proses Perendaman Pelepah Tanaman Salak Terhadap Waktu Pelepasan Serat (Retting) - Hartanto, Dwi; , Triastuti Rahayu, S.Si., M.Si (2015)
Utilization of midrib bark (Salacca edulis) in Indonesia is still very minimal . Midrib bark can be used as a source of natural fiber. Required method that can separate the midrib bark fibers quickly and produce fibers with good quality. The purpose of this study to determine the the effect of the addition of rumen fluid of cows and goats in the soaking process the midrib bark against fiber release time. This study used an experimental method with two factors, one factor is the type of rumen fluid (R1= cow rumen fluid and R2=goat's rumen fluid ) and factor 2 concentration of rumen fluid (K0=control, K1=10%, K2=20% and K3=30%) with 6 treatments 2 pieces of control. The parameters analyzed are retting time, pH, and the color of the fiber. Observations were carried out once a week for a month. The results showed that the addition of rumen fluid of cows and goats can affect the speed of retting time. In general, the pH of the soaking midrib bark decreased toward neutral, this happens because in the marinade cellulolytic bacterial activity occurs. The fastest retting time midrib bark plants occur in goat rumen fluid immersion concentration of 30% (K3R2), while the slowest in the first control (K0R1). Fiber results rumen fluid immersion cows and goats concentration of 20 % has a fiber color is best compared with other fibers.